Qinglong Zhidong Decoction Alleviated Tourette Syndrome in Mice via Modulating the Level of Neurotransmitters and the Composition of Gut Microbiota - Wang, Na; Wu, Xinchen; Yang, Qi; Wang, Dingyue; Wu, Zhao; Wei, Yuanyuan; Cui, Jieqiong; Hong, Li; Xiong, Lei; Qin, Dongdong (Frontiers in Pharmacology, 2022)
Background: Qinglong Zhidong Decoction (QLZDD), a traditional Chinese medicine (TCM) prescription, has been effectively used to alleviate Tourette syndrome (TS) in children. However, the therapeutic mechanism of QLZDD on TS has not been evaluated. Purpose: By a mouse model, the present study aims to elucidate the therapeutic effect and the possible therapeutic mechanism of QLZDD on TS. Methods: A 3,3-iminodipropionitrile (IDPN)-induced-TS mouse model was established. The mice were randomly divided into the control group, the model group, the haloperidol group, the low-, middle-, or high-QLZDD-dose group. QLZDD was administrated orally once a day for 4 weeks. The tic-like behavior was recorded weekly. Then, neurotransmitters and neurotransmitter receptors were analyzed by ELISA, immunohistochemistry (IHC), and quantitative reverse transcription PCR. Further, the alteration to intestinal flora was monitored by 16s rRNA sequencing, and the role of gut microbiota in the alleviation of TS by QLZDD was investigated. Results: QLZDD ameliorated the tic-like behavior significantly. QLZDD decreased the level of excitatory neurotransmitters such as Glu and DA and increased the level of the inhibitory neurotransmitter GABA. Moreover, upon the QLZDD treatment, the mRNA expression and the protein expression of D1R and D2R in the striatum significantly decreased and the mRNA expression and the protein expression of DAT and GABAR in the striatum increased. Interestingly, QLZDD modulated the composition of gut microbiota by increasing the abundance of Lactobacillus and Bacteroides and decreasing the abundance of Alloprevotella and Akkermansia. Conclusion: Collectively, QLZDD ameliorated TS in mice by restoring the balance of gut microbiota and neurotransmitters. This study revealed a promising role of QLZDD in the alleviation of TS and indicated a therapeutic strategy for fighting TS in clinical settings.